Providing physical health care for people accessing mental health services: Clinicians' perceptions of their role. (27th August 2018) - Clancy, Richard; Lewin, Terry J.; Bowman, Jenny A.; Kelly, Brian J.; Mullen, Antony D.; Flanagan, Karen; Hazelton, Michael J.
Abstract: The prevalence of health risk behaviours and associated poor physical health is high in people with severe mental illness. Mental health service guidelines and policies stipulate that mental health services should address physical health of people who access services. This study reports results from a large, interdisciplinary, cross‐sectional study exploring mental health clinicians' ( n = 385) views of role legitimacy in physical health service provision. All disciplines reported that mental health clinicians have a role to play in addressing the physical health of consumers. Among mental health clinicians, psychiatrists and mental health nurses received higher endorsement than allied health clinicians in relation to the provision of physical health care, with primary care providers including general practitioners also ranking highly. As community mental health services routinely appoint allied health staff to case management roles, a challenge for services and a challenge for clinicians are to ensure that physical health and the effects of medication are monitored appropriately and systematically. Online and telephone support services received relatively lower endorsement. As the availability of nonface to face services increases, there is a need to explore their utility in this population and where appropriate promote their uptake.